Conquest of the Banda Islands by the Vereenigde Oostindische Compagnie (1609–1621) - Yuwono, Ardi Tri; ter Braake , Gijsbert (Universitas Negeri Semarang, 2025)
The conquest of the Banda Islands by the Vereenigde Oostindische Compagnie (VOC) between 1609 and 1621 began with the arrival of the VOC in the Banda Islands in 1609, which marked the beginning of a systematic attempt to take control of the spice trade, especially nutmeg. The purpose of this study is to analyse the steps taken by the VOC in controlling the Banda Islands, explain the impact of the VOC conquest on the people of the Banda Islands and the spice trade network, and examine the historical actor roles, such as Jan Pieterszoon Coen, in this event. This study uses historical methods with a qualitative approach, as well as a historical-descriptive design, to reconstruct past events. The findings of this study show that the VOC implemented aggressive military strategies, including fortifications and massacres of local populations, as occurred in the Battle of Banda Neira Island, the Battle of Ay Island, the Battle of Rhun Island, and the Battle of Lontor Island. The impact of this conquest was severe, causing a drastic depopulation in the Banda Islands at the time, so that an estimated 90 percent of the indigenous population of the Banda Islands died. The VOC then repopulated the population with slaves to maintain plantation productivity in the Banda Islands.